2011 Florida Citrus Pest Management Guide: Citrus Black Spot - Megan M. Dewdney; Timothy S. Schubert; Mark R. Estes; Natalia A. Peres (EDIS, 2011)
PP-279, a 6-page fact sheet by Megan M. Dewdney, Timothy S. Schubert, Mark R. Estes, and Natalia Peres, provides citrus producers with essential information for management of this fungal disease that causes fruit blemishes and significant yield losses — regulatory considerations and recommended chemical controls. Published by the UF Department of Plant Pathology, December 2010.